An exploratory study of the drawings of selected Filipino preschool children - Encomienda, Ma. Agnes M.; Covar, Miriam M. (1996)
Drawings of Filipino preschoolers were analyzed to explore their content in terms of the features present, and to determine if their drawings follow a specific trend of growth. The relationship of drawing and the variables age, sex, and culture (home and school) were investigated as well. Thirty-two (32) Filipino preschoolers aged two to five (2-5) were observed while drawing spontaneously for three separate sessions and on a one-on-one basis. An equal number of male and female subjects were taken from two schools in Metro Manila which adhere to different approaches in education: i.e. Progressive and Traditional. Both the home and school environments were explored beforehand. "Home culture" was established from parents' responses to Child's Information Sheet while "school culture" was explored through research , interviews with administrators/ teachers and observations. Subjects were briefed first about the task, then engaged in the drawing task, and interviews as a last step. The proceedings were videotaped. Verbatim transcriptions of the videotapes, observations about the subjects' behavior, and drawing features seen in the drawings were recorded in a Drawing Observation Record (D.O.R). All data in the D.O.R. were analyzed both quantitatively and qualitatively. A Criteria for Analysis" which includes four categories was devised by the Researcher: (1) to establish a baseline or a norm by which to group or classify the drawings, (2) to "rate" each subject's drawing for the statistical analysis (multiple regression) and (3) to facilitate the comparison between the findings of this study and ideas stipulated in other studies on drawing. The categories in this criteria are based on the general trend of growth (in sequence & stages) as observed among children during the Pretest, and contrasted with the stages common among those which have been observed by other drawing theorists such as the stages proposed by Kelogg(1979) and Lowenfeld(1965). The findings of the study revealed the ff.: (1) Features present in the drawings of the preschool varied from age to age. Generally, with age, drawings progress from simple to more complex ones to which more details are being added. (2) the content of drawings included a variety of "scibbles" (indistinguishable marks); up-down strokes; dots; lines (straight, curved, zigzag, wavy); shapes (geometric & non-geometric); figures: objects and human figure ("stick", "shape", or "realistic"). (3) Themes drawn revolved around the self --- the child's interests and experiences, things a child sees in the immediate environment, or anything that holds a special significance for a child. (4) Differences in the drawings of males and females were not pronounced. (5) Culture which was defined in this study in terms of the type of school program (Traditional or Progressive) and the home environment was found not to have a significant effect on the content and themes of the Filipino preschoolers, although a few practices in school have been reflected in the drawings of some preschoolers (6) The drawings of the preschoolers showed a general sequence of growth. The results confirm and extend findings in previous studies that age is a factor in drawings and that drawings have a developmental characteristic.
Computer print-out.
Thesis (M.F.L.C.D.)--University of the Philippines, Diliman.
Keywords: Drawing ability in children -- Philippines; Child development; Creative ability in children -- Philippines; Preschool children -- Philippines